Development of kinesthetic differentiation of parameters of football player's movements using exercises Classic's - Georgiy Georgievich Polevoy (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2020)
The purpose of the study is to study the influence of the exercise «Classic's», during the training process of young players, on the general coordination abilities and their ability to kinesthetic differentiation of movement parameters. 50 children aged 8-9 years attended the pedagogical experiment, which lasted 9 months. 25 young players from the CG were engaged in the standard program, and 25 athletes from the EG additionally performed the exercise «Classic's» at each training session. The study investigated the level of development of coordination abilities (Shuttle run 3x10m) and kinesthetic abilities (Hitting the ball into the target) of children. After the end of the pedagogical experiment, the studied parameters in CG improved, but not significantly. At the same time, the EG indicators of General coordination improved from 10.5±0.8 sec to 8.5±0.5 sec (p<0.05), and the indicators of kinesthetic coordination abilities increased by 73.6%, this indicates the effectiveness of the exercise «Classic's» in the training activities of young players. If on trainings with young football players to use exercise «Classic's», their indicators of the General coordination and kinesthetic abilities will considerably improve. Also increase the emotional background of training, improve motor activity of young players, which is very important for children of primary school age.